Pole-Placement Position Control of a Hydraulic Robot Arm - Özsoy, C.; Kural, A.; Kuzucu, A. (SAGE Publications, 1994)
This paper discusses a single-input single-output discrete-time model developed to control joint position of a manipulator design for painting purposes. The input of the discrete-time model is the voltage into the control valve, and the output is the joint displacement. The model parameters are identified by using input-output data collected from the actual system. Recursive least-squares, square root, V-D factorization and variable forgetting factor methods were used for the estimation, and a good match between the model and actual system responses was obtained. The best estimation results were found by the U-D factorization algorithm according to the sum of the squared errors. Since identification results indicate a non-minimum phase system, a pole-placement self-tuning controller is designed for the purpose of joint trajectory control. The control signal computed off-line is applied to the electrohydraulic drive system and the perfect performance of the pole-placement controller is shown by the experimental studies.